Climate of origin influences how a herbivorous mite responds to drought-stressed host plants - Migeon, Alain; Auger, Philippe; Fossati-Gaschignard, Odile; Hufbauer, Ruth A; Miranda, Maëva; Zriki, Ghais; Navajas, Maria (Peer Community Journal)

(untitled)
Drought associated with climate change can stress plants, altering their interactions with phytophagous arthropods. Drought not only impacts cultivated plants but also their parasites, which in some cases are favored by drought. Herbivorous arthropods feeding on drought-stressed plants typically produce bigger offspring and develop faster. However, it is unclear how much responses to drought stress differ among populations of herbivore species. Here, we evaluate variability among populations of a major agricultural pest, the two spotted spider mite, Tetranychus urticae, in response to drought stress. We compare key life history parameters of twelve populations that originate from climates ranging from wet and cool Atlantic locations to medium to dry hot Mediterranean locations. We evaluated how plant drought stress affects four life history traits: development time, fecundity, sex-ratio and emigration rate in an experiment comparing well-watered and drought-stressed bean plants. Mites feeding on drought-stressed plants developed faster and attempted to leave leaves less often, and young females were more fecund. The mites from wet temperate climates exhibited greater plasticity between the two water regimes than mites originating from dryer and hot climates, suggesting that the climate in the area of origin influences mite response to drought.